Pengabdian Kepada Masyarakat Inovasi Pengembangan Teknologi Informasi Dalam Pengelolaan Koperasi Simpan Pinjam (KSP) - Pirmansyah Pirmansyah; Saeful Hamdi; Sofiansyah Fadli; Hairul Fahmi (Institut Teknologi dan Bisnis Semarang, 2024)
This service aims to explore the application of information technology in the management of Savings and Loan Cooperatives (KSP) to improve operational efficiency and quality of service to cooperative members. The problems faced by cooperatives include the lack of utilization of information technology, lack of operational efficiency, and limited services to members. To overcome these problems, this service uses a qualitative analysis approach through surveys, interviews, and observations. The purpose of this service is to provide practical guidance for KSP in adopting and implementing information technology, as well as contributing new knowledge in the literature on the application of information technology in KSP. The contributions of this service include providing concrete solutions to the problems faced by KSP, as well as increasing the theoretical understanding of the role of information technology in improving the performance of KSP. The results of the service show that the application of information technology has successfully improved the operational efficiency of KSP and the accessibility of services to members. The implications include the potential to improve the economic welfare of cooperative members and its relevance as a guide for policy makers in designing regulations that support the development of cooperatives. Thus, this service offers practical solutions and important knowledge contributions in improving the performance and relevance of KSPs in the digital era.